Swelling behaviour of compacted Maryland clay under different boundary conditions. Issue 6 (24th July 2018) - Yuan, S.; Buzzi, O.; Liu, X.; Vaunat, J.
Abstract : This paper presents an experimental study on the swelling response of compacted Maryland clay specimens subjected to hydration under a range of boundary conditions. The research is multi-scale with swelling tests complemented by comprehensive mercury intrusion porosimetry analyses. The objective of the experimental programme is to establish the locus of final swollen states (in terms of void ratio and swelling pressure) and assess its robustness by testing a range of boundary conditions or combinations thereof. Five initial soil conditions were tested and swelling was generated by flooding or incremental suction reduction by way of the osmotic technique. The paper shows that, for a given soil condition, there is no influence of the stress–volume path on the final swollen state. This observation was corroborated at the microscopic level by the mercury intrusion porosimetry. It was concluded that the effect of different stiffness can actually be analysed in terms of the maximum stress applied to the specimen. In particular, a clear correlation was identified between the macroscopic strains and the confinement applied during the test, regardless of the boundary conditions. Also, the conceptual model relating the water ratio and micro void ratio proposed by E. Romero and co-workers in 2011 was found to prevail, regardless of the boundary conditions.